A New Synthesis of Copper Nanoparticles and Its Application as a Beta-Hematin Inhibitor - Rana Abd Al-Aly Khamees Al-Refaia; Eman Alrikabi; Ahmed Ali Alkarimi; Rafaela Vasiliadou (Universitas Gadjah Mada, 2024)
To prevent the development of drug resistance and unwanted side effects, nanomaterials have been studied for their potential to inhibit beta-hematin, an important protein for the survival of malaria parasites. The use of nanomaterials as a medication against parasites and mosquito vectors has recently shown promising drug therapeutic strategies. One of the newest areas of interest in nanotechnology and nanoscience is the environmentally friendly production of nanoparticles. Green synthesis to produce metal nanoparticles is the most important strategy to overcome the possible dangers of toxic chemicals for a safe and harmless environment. For this study, copper nanoparticles (CuNPs) were synthesized using Iraqi basil leaf extract, demonstrating its novelty in nanosciences. The formation of CuNPs can be seen visually as a color shift from green to brownish. UV-vis absorption spectra, Fourier transform infrared (FTIR), X-ray diffraction (XRD), energy dispersive X-ray (EDX), and scanning electron microscopy (SEM) were used to characterize the synthesized nanoparticles. The surface plasmon resonance property (SPR) of CuNPs is revealed by UV-vis analysis, which shows a distinctive absorption peak at 420–430 nm, whereas SEM reveals the spherical shape of CuNPs with sizes ranging from 30 to 50 nm.